Chiral α-hydroxy acid-coadsorbed TiO2 photocatalysts for asymmetric induction in hydrogenation of aromatic ketones. Issue 89 (22nd October 2018) - Kohtani, Shigeru; Kawashima, Akira; Masuda, Fumie; Sumi, Momono; Kitagawa, Yuichi; Yoshioka, Eito; Hasegawa, Yasuchika; Miyabe, Hideto
Abstract : In enantioselective photohydrogenation of aromatic ketones on TiO2, the enantioselectivity is strongly affected by not only chiral reagents but also the crystalline phase, surface structure, and morphology of TiO2 . Abstract : Modification of titanium dioxide (TiO2 ) photocatalysts with chiral reagents was evaluated by the hydrogenation of aromatic ketones. The strong adsorption of chiral mandelic acid ( R )-MA on TiO2 was confirmed by comparing the inhibition effect IR values. The enantioselectivities were affected by not only the chiral reagents but also the TiO2 crystalline samples, suggesting that the interaction between aromatic ketones and MA on TiO2 should depend on the surface structure and morphology of TiO2 particles.